Design and motion analysis of a novel coupled mechanism based on a regular triangular bipyramid. (24th November 2016) - Gao, Huifang; Liu, Jingfang; Yu, Yueqing
Traditional methods and theories on synthesizing parallel mechanisms are not applicable to related researches on hybrid mechanisms, thus hampering the design of innovative coupled mechanisms. Polyhedrons with attractive appearance and particular geometrical construction provide many choices for coupled inventions. A novel mechanism with one translational degree of freedom based on a regular triangular bipyramid is proposed in this article. First, the basic equivalent geometrical model is spliced with new-designed components substituting for vertexes and edges by revolution joints (R-pairs) only. The expected motion for the basic coupled model can be achieved by adding links to modify the constraint sets and arrange spatial allocation of an elementary loop based on the screw theory. Then, the mobility of one branch is calculated to investigate the movability of the novel structure, and a Denavit–Hartenberg (D-H) model with properties of symmetry is implemented to investigate the inverse kinematic analysis. Furthermore, a numerical example is given to verify the correctness of analysis results and related motion simulation is conducted to illustrate the potential application of the proposed novel system as an executing manipulator for mobile robots.